Analisis 7P Terhadap Pemakaian Ulang yang Diintervensi oleh Kepuasan Pelanggan pada Layanan Gojek dan Grab Motor - Nabila, Sabrina Salma; Waluyo, Minto (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the influence of 7P on reuse intervened by customer satisfaction on Gojek and Grab Motor services. The data collection technique was through a questionnaire that showed there were 110 respondents each of Gojek and Grab service users spread throughout Indonesia. The collected data were then analyzed using Structural Equation Modeling (SEM). The results of the study revealed that product on Gojek has a positive and significant effect on customer satisfaction, while on Grab it has a positive but insignificant effect. Price on Gojek has a negative and insignificant effect, while on Grab it has a positive but also insignificant effect. Place, people, and physical evidence on Gab and Gojek have a positive but insignificant effect on customer satisfaction. Customer satisfaction intervention shows that only product on Gojek is significant in influencing reuse, while other variables such as price, place, people, and physical evidence on Gojek and Grab are insignificant. Promotion and process variables were not analyzed further, because they were excluded due to multicollinearity. Customer satisfaction has a positive and significant effect on reuse on Gojek and Grab services. Thus, although most of the 7P elements are insignificant, customer satisfaction remains an important factor in increasing reuse.